Last visit was: 21 Jun 2024, 16:39 It is currently 21 Jun 2024, 16:39
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Date
Tags:
Difficulty: Sub 505 Level,    Algebra,    Functions and Custom Characters,                            
Show Tags
Hide Tags
Math Expert
Joined: 02 Sep 2009
Posts: 93950
Own Kudos [?]: 633726 [25]
Given Kudos: 82413
Send PM
Math Expert
Joined: 02 Sep 2009
Posts: 93950
Own Kudos [?]: 633726 [3]
Given Kudos: 82413
Send PM
Manager
Manager
Joined: 14 Jan 2013
Posts: 114
Own Kudos [?]: 1544 [1]
Given Kudos: 30
Concentration: Strategy, Technology
GMAT Date: 08-01-2013
GPA: 3.7
WE:Consulting (Consulting)
Send PM
Manager
Manager
Joined: 20 Dec 2013
Posts: 183
Own Kudos [?]: 291 [1]
Given Kudos: 35
Location: India
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
1
Kudos
Option B.
(-2)*x=-12
(-2-1)(x+1)=-12
x+1=4
x=3
Math Expert
Joined: 02 Sep 2009
Posts: 93950
Own Kudos [?]: 633726 [0]
Given Kudos: 82413
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
Expert Reply
SOLUTION

For all numbers s and t, the operation * is defined by s*t = (s - 1)(t + 1). If (-2)*x = -12, then x =

(A) 2
(B) 3
(C) 5
(D) 6
(E) 11

Since \(s*t = (s - 1)(t + 1)\), then \((-2)*x = (-2-1)(x+1)=-3(x+1)\).

So, we are given that \(-3(x+1)=-12\) --> \(x+1=4\) -> \(x=3\).

Answer: B.
User avatar
Manager
Manager
Joined: 26 Feb 2015
Posts: 94
Own Kudos [?]: 205 [2]
Given Kudos: 43
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
1
Kudos
Can I please get an explaination to this? Completely clueless..

How do you conclude that s = -2 and t = x?
GMAT Club Legend
GMAT Club Legend
Joined: 19 Dec 2014
Status:GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Posts: 21835
Own Kudos [?]: 11733 [4]
Given Kudos: 450
Location: United States (CA)
GMAT 1: 800 Q51 V49
GRE 1: Q170 V170
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
2
Kudos
2
Bookmarks
Expert Reply
Hi erikvm,

This is an example of a "Symbolism" question (you'll likely see one of them on Test Day). The basic concept is usually pretty simple - the prompt will "make up' a math symbol, explain to you what it "means" mathematically, then ask you to use it to perform a calculation.

Since the * symbol makes people think about multiplication, I'm going to change it to a # symbol. Here, we're told....

S#T = (S-1)(T+1)

You are meant to take the numbers that S and T represent and place them into the calculation. So, as an example, if we had...

2#3 then that would equal (2-1)(3+1) = (1)(4) = 4

Knowing that, we're given....

(-2)#X = -12 and we're asked to solve for X

Let's 'substitute in' the (-2) and the X....

(-2 - 1)(X + 1) = -12

Now, you can do the algebra....
(-3)(X + 1) = -12
(X + 1) = 4
X = 3

Final Answer:

GMAT assassins aren't born, they're made,
Rich
Math Expert
Joined: 02 Sep 2009
Posts: 93950
Own Kudos [?]: 633726 [1]
Given Kudos: 82413
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
1
Bookmarks
Expert Reply
erikvm wrote:
Can I please get an explaination to this? Completely clueless..

How do you conclude that s = -2 and t = x?


Check other function questions in our Special Questions Directory:

Operations/functions defining algebraic/arithmetic expressions
Symbols Representing Arithmetic Operation
Rounding Functions
Various Functions
Target Test Prep Representative
Joined: 14 Oct 2015
Status:Founder & CEO
Affiliations: Target Test Prep
Posts: 19044
Own Kudos [?]: 22459 [1]
Given Kudos: 286
Location: United States (CA)
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
1
Kudos
Expert Reply
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

For all numbers s and t, the operation * is defined by s*t = (s - 1)(t + 1). If (-2)*x = -12, then x =

(A) 2
(B) 3
(C) 5
(D) 6
(E) 11



We are given that s * t = (s - 1)(t + 1).

Since (-2) * x = -12:

(-2 - 1)(x + 1) = -12

(-3)(x + 1) = -12

-3x - 3 = -12

-3x = -9

x = 3

Answer: B
GMAT Club Legend
GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5223
Own Kudos [?]: 4081 [0]
Given Kudos: 160
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

For all numbers s and t, the operation * is defined by s*t = (s - 1)(t + 1). If (-2)*x = -12, then x =

(A) 2
(B) 3
(C) 5
(D) 6
(E) 11

Problem Solving
Question: 113
Category:Algebra First-degree equations
Page: 76
Difficulty: 600


GMAT Club is introducing a new project: The Official Guide For GMAT® Quantitative Review, 2ND Edition - Quantitative Questions Project

Each week we'll be posting several questions from The Official Guide For GMAT® Quantitative Review, 2ND Edition and then after couple of days we'll provide Official Answer (OA) to them along with a slution.

We'll be glad if you participate in development of this project:
1. Please provide your solutions to the questions;
2. Please vote for the best solutions by pressing Kudos button;
3. Please vote for the questions themselves by pressing Kudos button;
4. Please share your views on difficulty level of the questions, so that we have most precise evaluation.

Thank you!



Given: For all numbers s and t, the operation * is defined by s*t = (s - 1)(t + 1). If (-2)*x = -12

Asked: x =?

s*t = (s - 1)(t + 1)
(-2)*x = -12
(-2-1)(x+1) = -12
-3x - 3 = -12
-3x = - 9
x = 3


IMO B
Tutor
Joined: 05 Apr 2011
Status:Tutor - BrushMyQuant
Posts: 1786
Own Kudos [?]: 2124 [0]
Given Kudos: 100
Location: India
Concentration: Finance, Marketing
Schools: XLRI (A)
GMAT 1: 700 Q51 V31
GPA: 3
WE:Information Technology (Computer Software)
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
Expert Reply
Top Contributor
Given that s*t = (s - 1)(t + 1) and (-2)*x = -12 and we need to find the value of x

To find (-2)*x we need to compare what is before and after * in (-2)*x and s*t

=> We need to substitute s with -2 and t with x in s*t = (s - 1)(t + 1) to get the value of (-2)*x

=> -2*x = (-2 - 1)(x + 1) = -3 *(x+1) = -12 (given)
=> x + 1 = \(\frac{-12}{-3}\) = 4
=> x = 4 - 1 = 3

So, Answer will be B
Hope it helps!

Watch the following video to learn the Basics of Functions and Custom Characters

User avatar
Non-Human User
Joined: 09 Sep 2013
Posts: 33651
Own Kudos [?]: 839 [0]
Given Kudos: 0
Send PM
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
GMAT Club Bot
Re: For all numbers s and t, the operation * is defined by s*t = [#permalink]
Moderator:
Math Expert
93950 posts